Land Movements Estimation in Amathus Archaeological Site in Limassol District with In- SAR DIn-SAR Methodologies - Makri, Despina; Agapiou, Athos; Hadjimitsis, Diofantos G.; Papoutsa, Christiana (My University, 2021)
Amathus archaeological site is one of the most important monuments (memorials), which remains for up to 2300 years. Last decades, archaeological sites, face anthropogenic and natural disturbances. One of those is the land movements that come from landslides or earthquakes. Improved remote-sensing techniques and new data more contemporary can assist in archaeology because it provides extensive area coverage and access in difficult-to-reach archaeological sites. In the present study, we investigate the use of Synthetic Aperture Radar Interferometry (InSAR) in land movement estimation near archaeological sites. We applied the D-InSAR (Differential Synthetic Aperture Radar Interferometry) methodology in Sentinel-1 data. These data are free and available from Copernicus Open Access Hub. The methodological framework was implemented in SNAP software (Sentinel Applications Platform), which is free and available from the European Space Agency. The analysis had three main steps: a) to prepare the data and check the suitability, b) the production of the interferogram, and c) the production of displacement map in meter units. The results have shown that in the area of interest, the hazard of land movement is low. The abstract should summarize the contents of the paper in short terms, i.e. 150–250 words.
Keywords: Amathus; Archaeological site; Land movement estimation